The Effective Use of Target Culture in Foreign Language Learning Environments: Düzce Case in Türkiye - Samet Türer; Filiz Evran Acar (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The study aims to determine the current implementations being used in foreign language education programs and to define how to use culture effectively in language learning environments according to the teachers’ ideas since language and culture are inseparable. Phenomenology was chosen as the design of the study. 17 English lecturers from the School of Foreign Languages of a government university in Türkiye were selected as the study group using purposive sampling. In the data gathering process, a semi-structured interview form was used, and the interview was carried out through face-to-face interviews. The data was analysed using the content analysis method and then coded and categorized under main themes, which were established based on the sub-questions of the study. In this regard, four main themes and 23 codes have been defined in detail with literature references by the researchers. According to the findings of the study, it is understood that there is a continuous interaction between language and culture. Therefore, one cannot be acquired fully without the other, and especially learning a language without its cultural context may lead to miscommunication. Consequently, culture should be integrated into each the language teaching and learning phase by integrating cultural elements into curriculums.